Duodenal perforation in an infant - Bozer, Ahmet Yüksel (The Turkish Journal of Pediatrics, 1961)
A duodenal perforation in a 2 1/2 month old baby was presented. The value of roentgenography in the diagnosis of perforation was emphasized.